Watershed-presegmented snake for boundary detection and tracking of left ventricle in echocardiographic images. - Jierong Cheng (IEEE Transactions on information technology in biomedicine)
In this paper, an automated method of boundary detection of the left ventricle (LV) is proposed. The method uses a watershed transform and morphological operation to locate the region containing the LV, then performs snake deformation with a multiscale directional edge map for the detection of the endocardial boundary of the LV